Pharmaceutical development specifics of new generic drug products in suspension for injection form on the Betaspan depot (Depos) example - O. I. Kachaput; S. M. Gureyeva; A. M. Goy (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
The range of combined domestic drug products in suspension for injections form with a specific purpose for the topical treatment of rheumatoid arthritis is limited, and available drug products are mainly submitted by foreign companies and their number does not solve the problem of providing patients with the qualitative and affordable drug products.